Evolving a comprehensive geomatics multi-criteria evaluation index model for optimal pipeline route selection - Hamid-Mosaku, I.A. (Taylor and Francis Ltd., 2020)
Selection of pipeline routes is a geospatial multi-criteria evaluation problem since it involves the assessment of technical, environmental and safety-related factors that influence pipeline system operations. This study determines the optimal pipeline route for transmission of oil and gas products using the Dangote Refinery Project in Nigeria as a case study. Pertinent route selection factors were identified and structured into the expert feedback model of the Analytical Network Process (ANP) for accurate prioritization. LANDSAT 8 imageries of the study area were processed and classified into various land use and land cover types, which were further modelled in ArcMap 10.2 GIS software for routing analysis. Findings reveal that the most highly prioritized factors for proper route selection were the environmental and geological factors, while the least prioritized was the economic factor. In the end, alternative Route 2 was identified as the optimal route among the four evaluated alternative routes because of its minimum route length, minimum passage length through sensitive settlement areas, and less number of river, stream and existing platformsâ crossings. Â© 2020, Â© 2020 Informa UK Limited, trading as Taylor & Francis Group.